Sensation Seeking and Online Gaming Addiction in Adolescents: A Moderated Mediation Model of Positive Affective Associations and Impulsivity - Hu, Jianping; Zhen, Shuangju; Yu, Chengfu; Zhang, Qiuyan; Zhang, Wei (Frontiers in Psychology, 2017)
Based on the Dual Systems Model (Somerville, Jones, & Casey, 2010; Steinberg, 2010) and the biosocial-affect model (Romer & Hennessy, 2007) of adolescent sensation seeking and problem behaviors, the present study examined how (affective associations with online games as a mediator) and when (impulsivity as a moderator) did sensation seeking influence online gaming addiction in adolescence. A total of 375 Chinese male adolescents (mean age = 16.02 years, SD = 0.85) from southern China completed anonymous questionnaires regarding sensation seeking, positive affective associations with online games, impulsivity, and online gaming addiction. Our findings revealed that sensation seeking, positive affective associations with online games and impulsivity were each significantly and positively associated with online gaming addiction in adolescents. Positive affective associations mediated the relationship between sensation seeking and online gaming addiction. Further, impulsivity moderated the relationship between positive affective associations and online gaming addiction, such that the association between positive affective association and online gaming addiction was stronger for high than for low impulsivity adolescents. These findings underscore the importance of integrating the biosocial-affect model and the Dual Systems Model to understand how and when sensation seeking impacts adolescent online gaming addiction.